Perubahan Tata Guna Lahan Terhadap Karakteristik Banjir di Kampus II UMS dengan HEC-HMS - ULINUHA, LAILA; , Ir. A. Karim Fatchan, M.T; , Gurawan Djati Wibowo, S.T., M.Eng (2016)
Changes to land of what happened on 2nd campus of UMS will affect the discharge. This can happen because the use of the land can change a value of C ( coefficient of land use ) and value CN.The study is done with a view to change to know of land and characteristic flood on 2nd campus of UMS with HEC-HMS and rational formula. HEC-HMS and rational formula the parameters to be aware of the addition of the reduction and the flood from the peak outflow ii flood campus before and after the mosque construction campus ii ums .This research using a number of primary and secondary data. The primary data obtained from direct observation in court to know basic channels slope. Secondary data obtained from literature study of related agencies such as data rain, topography data and space ii ums campus . Counting parameters based on existing data, can be concluded for a period of 2 annual rematch as follows. First floods and inundation on 2nd campus of UMS happened because of an inlet who enters keselokan less great intensity so water meresapnya and not a maximum capacity of a channel that lacking sufficient the presence of sedimentation cos. Both calculation discharge summits with rational calculation increase occurs worth 0,093 m3/s or 5.7 %. While the peak calculation discharge with a model unit hidrograf SCS been gained the rise in debit worth 0,004 m3 / s or 2.4 % .